Late diagnosis of Ebstein anomaly after pregnancy: A rare case report - Jesse Lesmana; Muhammad Ramadhan; Muhammad Barri; Sidhi Laksono Purwowiyoto; Zahra Nurusshofa (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2024)
Congenital heart disease is a concerning disease among those affected since it affects the patient's quality of life. One of which is Ebstein Anomaly (EA), with a prevalence of 1 in 200,0000 births with a clinical characteristic of displacement of the tricuspid valve that causes atrialization of the right-side heart. Women of childbearing age are at risk because they especially have asymptomatic EA, compromised to hemodynamic consequences, and risk of maternal complications. A 25-year-old woman visited the emergency department with worsening shortness of breath since last week, during rest, accompanied by decreased physical activity tolerance, bilateral ankle edema, cyanosis to the lips, and nail bed. She had echocardiography and cardiac multi-slice computed tomography to identify EA before and after her first child's birth. She was well controlled with a loop diuretic, phosphodiesterase type 5 inhibitor, and beta-blocker but could not care for her child due to her condition. The patient was discharged after symptoms subsided, awaiting further interventional evaluation. Although EA is rare, it has high morbidity and mortality, especially in women of childbearing age since it may be asymptomatic during childhood. Therefore, early recognition of EA is probably necessary for women who are planning pregnancy.